Effect of Cadmium in Biosorption of Lead by Lengkeng Seed and Shell (Euphoria logan lour) - Kurniawaty, Desy (Talenta Publisher, 2019)
In this study, the effect of of Cd(II) in biosorption of Pb(II) by lengkeng seed and sheel from a binary metal mixture was studied and compared with the single metal ion situation and other way. The purpose studied by the metal ion competition in the solution is to know the effect and the absorption capacity of one type of metal ion in a solution containing several metal ions inside which will be applied to the waste. The optimum conditions used were for Pb at pH 3 and Cd at pH 5 with a particle size of 250Î¼m. The results showed a decrease in the absorption of Pb metal ions reached 42.14% (for lengkeng sheel) and 57.07% (for lengkeng seed). And decrease of Cd metal ion to 68,11% for seed and 64,77% for lengkeng shell.